South–West of England’s Experience of the Safety and Tolerability Pirfenidone and Nintedanib for the Treatment of Idiopathic Pulmonary Fibrosis (IPF) - Barratt, Shaney L.; Mulholland, Sarah; Al Jbour, Khaled; Steer, Henry; Gutsche, Markus; Foley, Noeleen; Srivastava, Rajiv; Sharp, Charles; Adamali, Huzaifa I. (Frontiers in Pharmacology, 2018)
Purpose: Pirfenidone and nintedanib are two novel antifibrotic agents licensed for the treatment IPF. Prior to being approved for use in England for patients with FVC >50% and <80%, these were made available for all IPF patients under the Mild Patient Program (MPP) and Patient In Need Scheme (PIN). Prescribing of these medications is restricted to specialist centres. We sought to characterize the population of patients prescribed antifibrotics and determine the drug tolerability of these medications in the Northern hub of the Southwest of England regional ILD network. Methods: A retrospective analysis of all patients treated with antifibrotics between August 2012 and July 2017 was undertaken. Baseline characteristics including patient demographics and pulmonary physiology, in addition to drug tolerability and reasons for treatment cessation were collated. P<0.05 was considered statistically significant. Findings: A total of 164 patients, all with consensus diagnoses of IPF, were identified. Of these, 70.1% (115/164) received pirfenidone as their initial therapy. Baseline age, gender and pulmonary physiology did not differ significantly between groups. Drug discontinuation occurred most commonly due to adverse drug reactions events (ADRs) for both pirfenidone (40.0% (46/115)) and nintedanib (16.3% (8/49)). Anorexia, rash and gastrointestinal disturbance were reported most commonly as the reason for cessation of pirfenidone; anorexia, nausea and weight loss for nintedanib. Duration of therapy prior to discontinuation because of ADRs did not differ significantly between medication groups but patients with a baseline FVC<65% predicted, had a significantly shorter duration of pirfenidone prior to discontinuation due to ADRs, compared to those with a FVC 65-80% predicted. Multivariate logistic regression did not identify any independent baseline characteristics that predicted discontinuation of pirfenidone therapy prior to 52 weeks. Implications: IPF patients treated with nintedanib had comparable treatment emergent adverse event (TEAE) profiles in clinical practice to those reported in clinical trials. The TEAE profile of pirfenidone was higher than clinical trial data would suggest, although comparable to real-world datasets. Further work is required to explore the possible reasons underpinning this finding, including whether this is related to population co-morbidities or centre threshold. No new safety concerns were identified.